Sejarah dan makna relief Candi Singosari di Kabupaten Malang sebagai situs warisan budaya - Chamidah, Nur; Wifaqi, Hikmah; Wandhan Sari, Indang; Chamidah, Nur (Maliki Interdisciplinary Journal, 2026)
The Singosari Temple in Malang Regency is a significant cultural heritage site from the Singosari Kingdom, reflecting the history, spirituality, and socio-cultural dynamics of the past. This study aims to explore the history of the temple’s establishment and the meaning behind the ornaments and reliefs found within its structure. Built during the reign of King Kertanegara, the temple served as a center for Hindu-Buddhist religious activities and as the place where King Kertanegara’s ashes were enshrined following the kingdom’s collapse in 1292 due to an attack by the Kediri Kingdom. The temple’s reliefs and ornaments, such as Bhuta Kala, lotus flowers, and skulls, symbolize spirituality, protection from the god Shiva, and reverence for the Tantrayana tradition. However, some statues and ornaments have suffered damage due to natural disasters and the religious shift from Hinduism to Islam. This study highlights the importance of preserving Singosari Temple to ensure it remains an educational resource and historical tourism destination for future generations. By engaging both the government and local communities, conservation efforts can raise awareness of the temple’s historical and cultural value, ensuring its sustainability as part of Indonesia’s cultural heritage.